Factors affecting follower responses to movement calls in cooperatively breeding dwarf mongooses. (October 2022) - Cobb, Benjamin; Morris-Drake, Amy; Kennedy, Patrick; Layton, Megan; Kern, Julie M.; Radford, Andrew N.
Abstract : In social species, individuals maximize the benefits of group living by remaining cohesive and coordinating their actions. Communication is key to collective action, including ensuring that group members move together; individuals often produce signals when attempting to lead a group to a new area. However, the function of these signals, and how responses to them are affected by intrinsic characteristics of the caller and extrinsic factors, has rarely been experimentally tested. We conducted a series of field-based playback experiments with habituated wild dwarf mongooses, Helogale parvula, a cooperatively breeding and territorial species, to investigate follower responses to movement calls. In our first experiment, we found that focal individuals were more likely to respond to playback of 'movement calls' than control 'close calls', indicating movement calls function as recruitment signals. In a second experiment, we found that focal individuals responded similarly to the movement calls of dominant and subordinate groupmates, suggesting that dominance status (an intrinsic factor) does not influence receiver responses. In a final experiment, we found that individuals responded to the simulated presence of a rival group, but that this outgroup conflict (an extrinsic factor) did not affect responses to movement calls compared to a control situation. This may be because attention is instead focused on the potential presence of an imminent threat. By using playbacks to isolate the acoustic signal from physical movement cues, our results provide experimental evidence of how movement calls help leaders to attract followers and thus adds to our understanding of recruitment signals more generally. Highlights: We used playback experiments to study responses to dwarf mongoose movement calls. Movement calls elicited a movement response in focal subordinate group members. Receivers responded equally to calls of dominant and subordinate groupmates. A simulated rival group threat did not affect responses to movement calls.